WE ARE ALL AMBIVERTS NOW introverts, ambiverts and extroverts in the executive suite. - MOORE, KARL (ROUTLEDGE, 2025)
Based on real-world evidence from senior executives and successful entrepreneurs, this book argues that an effective leader must act like an ambivert: an introvert at times and an extrovert at others.Thanks to landmark books such as How to Win Friends and Influence People, many professionals think that only extroverts can be standout leaders, but Karl Moore's interviews with over 750 CEOs from around the world prove that introverts make excellent leaders too. These insights make clear that the optimal leadership style is ambivert, with senior leaders combining introversion-being excellent listeners and thinking before they speak-and extroversion-inspiring and connecting with their teams. This book teaches how introverts and extroverts work, manage, and lead effectively and how readers can be better leaders regardless of their natural communication style. It empowers leaders to celebrate the strengths of their personality type while being flexible and to understand when to incorporate the strengths of other types into their leadership approach to be more effective. While showing how to identify and utilize the approach that is best for a given situation, it also highlights the potential weaknesses of the ambivert's chameleon nature and emphasizes the importance of leaders staying true to themselves in any situation.Current and aspiring leaders, as well as entrepreneurs and MBA and executive education students, will understand how to develop and maximize the perfect blend of introversion and extroversion as this book guides them through a range of potential situations encountered in the workplace.
Keywords: Leadership.; Introverts.; Extraversion.; elektronické knihy; electronic books